Gant-Miwa-Thiersch-Yoshida Method for Complete Rectal Prolapse - Yoshida, Hideaki; Yoshida, Tetsuro; Sasaguchi, Masatoshi (Nippon Daicho Komonbyo Gakkai Zasshi, 2001)
In Japan, simple transanal operations have been applied for rectal prolapse than rather extensive laparotomy, which is common in Europe and America. Dr. Norisada Miwa, who revised the original Gant operational method, did not specifically write the method in his paper, but he orally suggested that the rectal mucosa should be pinched and tied like a tiedyeing method for cloth. In the search for better results with the Gant-Miwa operation, the materials and methods have been improved in hospitals. However, the recurrence rate is rather high, dispite these efforts. We also improved the method, creating the Miwa-Thiersch-Yoshida Method, and we have used it since 1975. In the operation, a strip of fascia is taken from the front part of the thigh, to use for tightening the anus. However, sometimes the fasia was too thin for the purpose, especially in an elderly patient. On this poist, an orthopedic surgeon advised me that fascia of the lateral part of the thigh is stronger. Since then, we have been utilizing a strip of the fascia lata, of size 2.0cm×14cm, excised from the lateral part of the thigh, and the operational results have improved. The postoperative result over 20 years is good, with a recurrence rate of less than 10%. This evidence reveals that autotransplantation of the fascia lata is a quite effective method as a supplementary addition to the Gant-Miwa method for rectal prolapse.